2012
DOI: 10.1021/ml300146q
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Phenylaminopyridine Derivatives as Novel HIV-1 Non-nucleoside Reverse Transcriptase Inhibitors

Abstract: ABSTRACT:We identified a novel class of aryl-substituted triazine compounds as potent non-nucleoside reverse transcriptase inhibitors (NNRTIs) during a high-throughput screening campaign that evaluated more than 200000 compounds for antihuman immunodeficiency virus (HIV) activity using a cell-based full replication assay. Herein, we disclose the optimization of the antiviral activity in a cell-based assay system leading to the discovery of compound 27, which possessed excellent potency against wild-type HIV-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…Kim et al identified a novel class of aryl substituted pyrazole compounds as potent non-nucleoside reverse transcriptase inhibitors (NNRTIs) for anti-human immunodeficiency virus (HIV) activity using a cell-based full replication assay. The optimization of the antiviral activity leading to the discovery of compound 411 which possessed excellent potency against wild-type HIV-1 (EC 50 = 0.2 nM) as well as viruses bearing Y181C and K103N resistance mutations in the reverse transcriptase gene [ 309 ]. Ndungu et al the synthesis and a SAR strategy that led to the discovery of novel pyrazole derivatives as potent measles virus (MeV).…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Kim et al identified a novel class of aryl substituted pyrazole compounds as potent non-nucleoside reverse transcriptase inhibitors (NNRTIs) for anti-human immunodeficiency virus (HIV) activity using a cell-based full replication assay. The optimization of the antiviral activity leading to the discovery of compound 411 which possessed excellent potency against wild-type HIV-1 (EC 50 = 0.2 nM) as well as viruses bearing Y181C and K103N resistance mutations in the reverse transcriptase gene [ 309 ]. Ndungu et al the synthesis and a SAR strategy that led to the discovery of novel pyrazole derivatives as potent measles virus (MeV).…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“… 1 Among these, S. aureus accounts for 16% of HAIs and is responsible for more deaths in the U.S. annually than HIV/AIDS. 1 3 The organism’s high morbidity and mortality rates are, in part, attributable to the fact that S. aureus has developed resistance to currently available antibiotics. 4 The quinolone class of antibiotics was once a predominant treatment option for S. aureus infections; 5 however, due to increasing quinolone resistance, these drugs continue to have diminishing efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…The first one is a group of "phenylaminopyridine" derivatives that inhibit HIV-1 replication [22]. Table 2 and Fig.…”
Section: Selected Systemsmentioning
confidence: 99%
“…We show the usefulness of our new model by presenting and analyzing structure-activity relationship results for the inhibition of HIV-1 WT replication by some phenylaminopyridine (PAP) derivatives [22] and for the inhibition of cell growth by several 1-azabenzanthrone derivatives [23]. Recently a series of compounds based on a 4-phenyl-2-phenylaminopyridine scaffold that are potent and selective inhibitors of Traf2-and Nck-interacting kinase activity have been described [24].…”
Section: Introductionmentioning
confidence: 99%